Quantum energy rating method for competitive performance forecasts in continental hockey league matches - Sivakov, V. I.; Aitkulov, S. A.; Cherkasov, I. F.; Perepelyukova, E. V.; Kravtsova, L. M. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to provide energy rating basis for the competitive performance forecasts in the continental ice hockey league matches. The study was designed to apply a quantum energy and functional state rating method to ice hockey players. The parameters rated in the study were as follows: energy system colorations, shapes and content of the informational vertical square and game progress circle - to assess the performance potentials and special fitness of the players and forecast the competitive result. The competitive performance profiling studies showed the ice hockey team performance being well rated by the energy level colorations (low, moderate and high) and energy shapes indicative of the spinal, neuro-muscle and functional energy centers performance. The energy system form may be changed from the horizontal to vertical to replenish the team red-color energy.